STUDI DESKRIPTIF PENERAPAN MEDIA TEKS VISUAL DALAM PEMBELAJARAN CERPEN SISWA KELAS XI MA RIYADHUL ULUM - Warohmah, Mawadah; Hindun; Ghani, Annuria; Nafidah, Aiska (Universitas Hamzanwadi, 2026)
The purpose of this research is to describe the implementation of the Constructivist-Based Visual-Creative Learning Model using visual text media in short story writing, and to examine its impact on students' writing quality. The scope is limited to the analysis of the learning process and the evaluation of short story results from 30 11th-grade students at MA Riyadhul Ulum. The method employed is descriptive evaluative, based on Constructivism theory and the Project Based Learning (PjBL) Model. Data were analyzed through Performance Tests (Writing Test) assessed using a rubric (four aspects of writing quality) and converted to percentages based on Nurgiyantoro's criteria (2013). The findings indicate that visual text media provided a significantly positive impact. All students (100%) achieved the Good (B) to Excellent (A) category, with 73% of students reaching the Excellent category (A). The interesting fact is that the visual media (sequential images and interesting video) effectively served as an imagination stimulant and a